A Rare Case of Hemorrhagic Shock: Morel-Lavallée Lesion - Lieke Claassen; Myriam Anna Franssen; Erik Robert de Loos (Clinical Practice and Cases in Emergency Medicine, 2019)
Hemorrhage is a major cause of death among trauma patients. Controlling the bleeding is essential but can be difficult when the source of bleeding remains unidentified. We present a 67-year-old healthy male with a hypovolemic shock after a suicide attempt by jumping from a height. Apart from a bilateral pneumothorax with multiple rib fractures, a femur fracture and spine fractures, computer tomography (CT) revealed a closed, degloving injury of the back, also known as a Morel-Lavallée lesion. Hemodynamic instability due to hemorrhage caused by a Morel-Lavallée lesion in the lumbar region is very rare and easily overlooked. This case demonstrates the importance of clinical signs of Morel-Lavallée, and illustrates the need for total body CTs to exclude other locations of bleeding and to detect contrast extravasation. This report also discusses the possible treatment options for Morel-Lavallée lesions.